Association Between Spatial Justice Indicators and Perceived Quality of Life Among Residents of Post-Industrial Urban Neighborhoods in Palembang, Indonesia - Napitupulu, Christian; Amanda, Vita; Yermekova, Aylin (HM Publisher, 2026)
Urbanization and post-industrial transitions have created spatial inequities that may influence residents’ quality of life (QoL). This cross-sectional analytical study examined the association between spatial justice indicators and perceived quality of life among 384 adult residents from three post-industrial neighborhoods (Area A, Area B, and Area C) in Palembang, South Sumatra, Indonesia. Data were collected using validated questionnaires measuring spatial justice indicators (green space access, healthcare access, public transport access, community center access), neighborhood safety, social cohesion, governance participation, and perceived QoL using an adapted WHO Quality of Life Brief instrument. Among the 384 respondents (mean age 42.0 ± 11.0 years; 50.3% female), 289 (75.3%) reported good QoL. Multivariate logistic regression revealed that high spatial justice index (aOR=3.49; 95% CI: 2.25–5.43; p<0.001), high governance participation (aOR=2.59; 95% CI: 1.85–3.62; p=0.002), green space access (aOR=2.12; 95% CI: 1.63–2.76; p=0.004), healthcare access (aOR=2.01; 95% CI: 1.57–2.58; p=0.007), neighborhood safety (aOR=1.85; 95% CI: 1.32–2.60; p=0.003), and social cohesion (aOR=1.68; 95% CI: 1.18–2.39; p=0.012) were significantly associated with good QoL. The Hosmer–Lemeshow test (p=0.684) and Nagelkerke R²=0.348 confirmed adequate model fit. Spatial justice indicators, particularly green space and healthcare accessibility, governance participation, and neighborhood safety, were independently associated with better perceived QoL in post-industrial communities